THE ASSESSMENT OF ECONOMICAL LOSS CAUSED BY FLOODS AND FLASH-FLOODS BY USING COMPUTER TECHNIQUES. CASE STUDY: LOPĂTARI VILLAGE, SLĂNIC RIVER - COSTACHE R. (Aerul şi Apa: Componente ale Mediului, 2015)
The present study aims to provide an example of the assessment of economical loss caused by floods and flash-floods, by integrating GIS techniques of hydraulic and hydrological modelling. The case study was performed in Lopătari village, which is located in the upper area of Slănic River, one of the most affected areas by floods and flash-floods. The flood event produced on 29.V.2012 was considered in order to perform this study. Thus, a flood hydrograph was simulated by using software HEC-HMS 3.5, based on hourly precipitation data from Bisoca meteorological station from 29.V.2012. The peak discharge resulting from the hydrological modelling software was used in HEC-RAS 4.1 hydraulic modelling software in order to determine the extent of flooding band, the number of the affected elements and the local economical loss. Finally, 21 flooded buildings were identified and 550 m of affected road, the estimated economical damage being about 800,000 RON.